The Degree of COVID-19 and Preeclampsia at Dr. Soebandi Hospital, Jember - Sisca Puji Rahayu; Angga Mardro Raharjo; Dita Diana Parti; Yuli Hermansyah; Pipiet Wulandari; Nurul Istinaroh (Jurnal Respirasi, 2023)
Introduction: The risk of preeclampsia increases due to COVID-19. COVID-19 was the leading cause of Indonesia's high maternal mortality rate in 2021, with 2,982 cases. COVID-19 cases affected the maternal mortality rate in East Java, reaching 234.7 per 100,000 live births. Jember ranks first with the highest number of deaths of pregnant women in East Java. This study aimed to examine the relationship between the severity of COVID-19 and the degree of preeclampsia at Dr. Soebandi Hospital, Jember. Methods: This was an analytic observational study with a cross-sectional design. This study was conducted from March to April 2023. A total of 27 samples of pregnant women with COVID-19 were taken using the total sampling method in 2020-2022 at Dr. Soebandi Hospital, Jember, and analyzed using SPSS with the Spearman statistical test. Results: This study found that pregnant women with mild cases of COVID-19 were 9 cases, 16 cases were moderate, and 2 cases were severe. There were 15 cases of pregnant women with no preeclampsia and 12 cases with severe preeclampsia. Conclusion: There was no relationship between the severity of COVID-19 and the degree of preeclampsia at Dr. Soebandi Hospital, Jember.